The influence of age and BMI on foot progression angle in knee osteoarthritis: a correlation analysis - Rastogi, Aavrati; Kalia, Roop B.; Meena, Pradeep K. (International Journal of Research in Medical Sciences, 2025)
Background: Knee osteoarthritis (KOA) is a degenerative joint disease, often associated with age and body mass index (BMI), critical demographic factors influencing its progression. The Foot Progression Angle (FPA), a measure of foot alignment, has been studied as a potential contributor to the development and progression of KOA. Methods: A comprehensive prospective analysis investigated the relationship between age, BMI, and FPA in individuals diagnosed with KOA. The study included data from participants categorized based on their Kellgren-Lawrence (K/L) grades: K/L grade II and K/L grade III. Correlation coefficients (R) and p values were meticulously calculated to assess these relationships' strength and statistical significance. Results: Our correlation analysis in KOA (K/LII and III) showed weak, non-significant correlations between age, BMI, and FPA. Specifically, age was linked with FPA at -0.1415 (p value 0.3499) in K/L 2 and -0.1257 (p value 0.33) in K/L grade 3, while BMI correlations were -0.125 (p value 0.40) in K/L 2 and -0.1402 (p value 0.27) in K/L 3. Conclusions: While BMI and age are significant factors in KOA, their relationship with FPA is weak and insignificant. This finding paves the way for further research to explore other biomechanical factors that may play a more substantial role in knee OA progression.